Evaluation of surface water bodies still preserved in the city of Manaus: anthropogenic factors in the alteration of water quality - Ferreira, Sávio José Filgueira; Lages, Anderson da Silva; Rosas, Adriana Freitas; Monteiro, Maria Terezinha Ferreira; da Silva, Márcio Luiz; de Souza Bastos, Alexandre; Gastmans, Didier [UNESP]; da Conceição, Adriana Castro (Revista Brasileira de Geografia Fisica, 2023)
A B S T R A C T Manaus is intersected by bodies of water called igarapés (canoe path). These bodies of water are under polluting pressure. One example is the Matrinxã creek, located in the area of influence of the sanitary landfill. The objective of this study was to evaluate the surface waters close to the Manaus sanitary landfill and compare the conditions of these waters with the natural waters of the region. Biweekly collections were carried out and environmental variables were analyzed in the periods 2011-2015 and 2021-2022. Water collections were made with sterilized polyethylene bottles and samples were collected near the middle of streams, with the aid of Teflon sticks. Then, the samples were transported to the laboratory of Environmental Chemistry at INPA, where pH, electrical conductivity, dissolved oxygen and ions were analyzed. The results showed that the acidity values of the Açu, Barro Branco and Sauim Castanheira streams still retained the characteristics of the acidic waters of Manaus (pH less than 5.0). However, the Matrinxã stream had a pH above 6.0, with waters highly conductive (~200 µS cm-1). Nitrate values in the Matrinxã waters are ten times higher than the natural value (7.83 mg L-1). PCA showed that ammonium and nitrate nitrogenous are silicate inhibitors. Given the above, the Açu stream was the best marker of natural conditions, while the Barro Branco and Sauim Castanheira streams, with intermediate conditions, with some signs of anthropogenic influence, while the Matrinxã stream is the most impacted by the urban pressure of the city of Manaus.
Avaliação de corpos de água superficiais ainda preservados na cidade de Manaus: fatores antropogênicos na alteração da qualidade das águas
Keywords: Açu Streams; Barro Branco Streams; Matrinxã streams